(untitled) (Bangladesh Journal of Nutrition, 2021)
The COVID-19 outbreak is a worldwide hazard and a pandemic. It affects primarily the respiratory system of the infected persons. The severity of infection depends on various factors such as individual health, age, lifestyle, gender, dietary habits, environment, and medications. COVID-19’s catastrophic results are exacerbated by a high BMI and chronic conditions. The study’s goal was to look at the effects of antioxidant foods on immune function and their possible involvement in the treatment of COVID-19 infection. The human immune cell is always active, and the activity of the immune system is improved when there is an infection requiring energy sources and substrates taken from the food. A range of vitamins and trace minerals has been found to have crucial functions in enhancing immune function and decreasing the chance of infection. The gut microbiota strives to empower and regulate the immune system. Dietary methods for achieving a healthy microbiome can also improve the immune system. According to worldwide standards, the best way to maintain the immune system is to consume a healthy balanced diet rich in plant and animal foods, as well as appropriate prebiotic and probiotic prophylactic supplements. Bangladesh J. Nutr. Vol. 34, December 2020, P: 77-86